2018
DOI: 10.1002/ana.25271
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar atrophy and its contribution to cognition in frontotemporal dementias

Abstract: This study is the first to identify distinct patterns of cerebellar atrophy across FTD syndromes, which in turn relate to discrete cognitive dysfunctions, after accounting for the effect of cerebral atrophy. These findings extend our understanding of the cerebellum and point to its involvement across an array of processes beyond the domain of motor function. Ann Neurol 2018;83:98-109.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 76 publications
2
36
1
Order By: Relevance
“…The thalamus exhibits dense connections to the hypothalamus which may also potentially influence changes in body composition through neuroendocrine inputs, and has been previously implicated in changes in eating behavior in FTD and BMI in ALS . Changes in body composition (android: gynoid ratio and VAT area) also correlated to atrophy of the cerebellum, which has again been implicated in overeating behavior in FTD, and a range of autonomic, cognitive, emotional functions, and reward processing …”
Section: Discussionmentioning
confidence: 97%
“…The thalamus exhibits dense connections to the hypothalamus which may also potentially influence changes in body composition through neuroendocrine inputs, and has been previously implicated in changes in eating behavior in FTD and BMI in ALS . Changes in body composition (android: gynoid ratio and VAT area) also correlated to atrophy of the cerebellum, which has again been implicated in overeating behavior in FTD, and a range of autonomic, cognitive, emotional functions, and reward processing …”
Section: Discussionmentioning
confidence: 97%
“…For example, impairments on emotion attribution and faux-pas tasks in bvFTD have been shown to correlate with lateral temporal cortex integrity, including the right anterior temporal lobes (ATLs)59,60 and superior temporal cortices,31,61 as well as medial and lateral parietal regions such as the TPJ, precuneus,54 and PCC 61. Emergent evidence has further implicated cerebellar degeneration in modulating aspects of cognitive dysfunction62 as well as ToM difficulties on the Frith–Happé animations task 16. Longitudinal studies tracking how the evolution of ToM dysfunction in bvFTD relates to encroachment of pathology in temporoparietal cortices and the cerebellum are clearly warranted.…”
Section: Behavioral-variant Of Frontotemporal Dementia (Bvftd)mentioning
confidence: 99%
“…Limitations of the Talairach-Tournoux brain atlas are thus circumvented, enabling more accurate depiction than whole-brain methods offer. Previously conducted functional MRI studies relying on SUIT have successfully identified morphologic changes of cerebellar subregions in several neuropsychiatric diseases (Chen et al, 2018; Cocozza et al, 2017; de Azevedo et al, 2017; Piccinin et al, 2017). In addition, these studies showed that SUIT template preserves more anatomical detail of the cerebellum and allows for better localization of cerebellar findings than the commonly-used whole brain Voxel-based morphometry(VBM) MNI template.…”
Section: Introductionmentioning
confidence: 99%